Power and Pleasure of Ideas: The Maine Humanities Council and the Public Humanities in Maine - Anderson, Hayden (Maine Policy Review, 2015)
By providing public humanities programs and opportunities throughout the state, the Maine Humanities Council (MHC) envisions the communities of Maine transformed by the power and pleasure of ideas. This article describes several different public humanities programs sponsored by the MHC—New Books, New Readers, Literature & Medicine, Veterans Book Group, and Let’s Talk About It—and the commission’s grant programs. According to Hayden Anderson, there is a key premise underlying everything the MHC does: gathering people together to read, share, talk, and think together makes a difference.
Keywords: public humanities; facilitated discussion; Maine